Characteristics of CO2 Emission on Peatland Under Oil Palm Trees - Winarna, Winarna; Santoso, Heri (Jurnal Penelitian Kelapa Sawit, 2020)
The research aim was studying the characteristic CO2 emission from peatland under oil palm trees as a relationship with environmental factors of specific locations in the Labuhan Batu District of North Sumatra. CO2 gasses were sampling by closed chamber technique and their concentration was measured by portable micro Gas Chromatograph CP 4900. The observation of environmental factors as the variable that affected to CO2 emission included soil temperature (TS), atmosphere temperature (TA), soil moisture on 0-5 cm of soil depth (SM5), soil moisture on 0-30 cm of soil depth (SM30), and pH of peat (A). The relationship model of CO2 emission with environmental factors analyzed by Spearman correlation and multivariant regression. Stepwise regression was applied for multivariant regression to identify the environmental factors that have a relationship with CO2 emission with significant analysis in 5 % of the threshold. Variance inflation factor (vif) was applied to identify the multicollinearity problem of the model from multivariant regression. The Spearman correlation showed the A (pH) of environmental factors have the highest correlation coefficient with the middle category (R=0.637). The stepwise regression showed the CO2 emission have been significantly affected by soil moister SM30 and A (n = 216; p < 0.05) with vif value < 3. The regression model from multivariant regression was CO2 = 7.394*A – 0.008*SM30 – 16.659 with R2 = 0.420. In the partial, there was a relationship of CO2 with soil moisture in the field capacity condition. The highest CO2 emission occurred at soil moisture of 354 – 376% w w-1 and decreased while the soil moisture increases overring the field capacity condition. The CO2 emission was decreased while the peat soil was drying at under the critical of water content caused the peat soil hydrophobicity was increasing.